Fecal microbiota transplantation ameliorates gut microbiota imbalance and intestinal barrier damage in rats with stress‐induced depressive‐like behavior. (10th May 2021) - Rao, Jingjing; Xie, Ruining; Lin, Li; Jiang, Jian; Du, Lei; Zeng, Xindie; Li, Gongying; Wang, Chunmei; Qiao, Yi
Abstract: The gut–microbiota–brain axis is the most important complex and bidirectional pathway between the gastrointestinal tract and the central nervous system. This study investigated the potential of microbe‐induced gut‐to‐brain signaling to modulate the effect of stress on depressive‐like behavior, intestinal barrier, and neuroinflammation. Result showed that fecal microbiota transplantation increased the consumption of sucrose solutions and decreased the immobility time in forced swimming test. This treatment also increased Firmicutes and decreased Bacteroidetes and Desulfobacterota at phylum levels; reduced the loss of villi and epithelial cells; suppressed the inflammatory cell infiltration in the ileum; increased the expression of ZO‐1, occludin; protected the mucosal layer function; and suppressed the high levels of inflammasomes ( NLRP3, ASC, caspase‐1, and IL‐1β ) in rat brain. In summary, fecal microbiota transplantation improves the depressive‐like behavior, alters the gut microbiota imbalance, and alleviates the intestinal tract inflammation, intestinal mucosa disruption, and neuroinflammation in rats induced by chronic unpredictable mild stress. Abstract : Stress situations could lead to an imbalance in the gut microbiota that in turn leads to production of inflammatory mediators. Changes in the gut microbiota may damage the gut barrier and produce higher levels of inflammatory cytokines. Products from microbiota impairment or periphery pro‐inflammatory cytokines could disrupt the blood–brain barrier and cross to the brain increasing cytokines (NLRP3, ASC, Caspase‐1, IL‐1β) releasing in the brain.